2022
DOI: 10.3390/genes13040705
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Epigenetic Modifications in Late Complications in Type 1 Diabetes

Abstract: Type 1 diabetes is a chronic autoimmune disease in which the destruction of pancreatic β cells leads to hyperglycemia. The prevention of hyperglycemia is very important to avoid or at least postpone the development of micro- and macrovascular complications, also known as late complications. These include diabetic retinopathy, chronic renal failure, diabetic neuropathy, and cardiovascular diseases. The impact of long-term hyperglycemia has been shown to persist long after the normalization of blood glucose leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 115 publications
0
9
0
3
Order By: Relevance
“…In the kidney, the interplay between miRNAs and epigenetic factors has been demonstrated not only in cancer, but also in common renal diseases [33], highlighting a key role in the development and progression of diabetic nephropathy. In human renal cell carcinoma (RCC), miRNA-101 negatively regulates the histone methyltransferase Enhancer of Zeste Homolog 2 (EZH2) promoting an antiproliferative effect.…”
Section: Micrornas Dependent Epigenetic Regulation Of Kidneymentioning
confidence: 99%
“…In the kidney, the interplay between miRNAs and epigenetic factors has been demonstrated not only in cancer, but also in common renal diseases [33], highlighting a key role in the development and progression of diabetic nephropathy. In human renal cell carcinoma (RCC), miRNA-101 negatively regulates the histone methyltransferase Enhancer of Zeste Homolog 2 (EZH2) promoting an antiproliferative effect.…”
Section: Micrornas Dependent Epigenetic Regulation Of Kidneymentioning
confidence: 99%
“…Взаємодію генів і середовища при ЦД2 та інших захворюваннях можна частково пояснити епігенетичними механізмами, які здійснюють вплив на експресію генів шляхом їх ковалентної модифікації, не зачіпаючи первинну послідовність ДНК [3][4][5][6]. Прикладом впливу епігенетичних механізмів (таких як метилювання ДНК, модифікація гістонів і мікро-РНК) є феномен метаболічної пам'яті, коли вплив тривалої гіперглікемії зберігається ще довгий час після нормалізації рівня глюкози в крові [7].…”
Section: оглядиunclassified
“…Роль головних ферментів у процесах трансметилювання у фолатному циклі [12]. пригнічують або збільшують експресію генів [7,13]. Численні дослідження показали, що метилювання ДНК відіграє ключову роль у зростанні захворюваності на ЦД2 [6,8,9,14,15].…”
Section: процеси трансметилювання в регуляції фолатного циклуunclassified
“…A primary multi-organ effect originating from deregulated glycemia consists in disrupting three major biological functions: DNA expression, RNA transcription, and protein translation. Studies have indicated that hyperglycemia may increase DNA mutations, DNA breaks, genomic instability, and particularly epigenetic dysregulation [ 33 , 34 ]. Accordingly, hyperglycemia and a constellation of downstream factors transform the cellular native epigenetic architecture, rendering a de novo code that largely alters cellular physiology [ 35 ].…”
Section: Introductionmentioning
confidence: 99%